Effects of Buffer Layer on Structural Properties of Nonpolar (11<semantics><mover accent="true">2¯</mover></semantics>0)-Plane GaN Film - Jianguo Zhao; Boyan Suo; Ru Xu; Tao Tao; Zhe Zhuang; Bin Liu; Xiong Zhang; Jianhua Chang (Crystals, 2023)
Nonpolar (11<semantics><mover accent="true">2¯</mover></semantics>0) a-plane GaN films were grown on semipolar (1<semantics><mover accent="true">1¯</mover></semantics>02) r-plane sapphire substrates using various buffer layers within a low-pressure metal organic chemical vapor deposition system. The structural properties of nonpolar a-plane GaN films were intensively investigated by X-ray diffraction and Raman spectra measurements. A set of buffer layers were adopted from a GaN layer to a composite layer containing a multiple AlN layers and a gradually varied-Al-content AlGaN layer, the full width at half maximum of the X-ray rocking curves measured along the [0001] and [10<semantics><mover accent="true">1¯</mover></semantics>0] directions of a-plane GaN were reduced by 35% and 37%, respectively. It was also found that the basal-plane stacking faults (BSFs) density can be effectively reduced by the heterogeneous interface introduced together with the composite buffer layer. An order of magnitude reduction in BSFs density, as low as 2.95 × 104 cm−1, and a pit-free surface morphology were achieved for the a-plane GaN film grown with the composite buffer layer, which is promising for the development of nonpolar GaN-based devices in the future.